A inclusão de alunos surdos no Instituto Federal de Educação, Ciência e Tecnologia do Amazonas: e agora,o que fazer? - Freitas, Cristiane Rodrigues de (2019)
This masters research arose during my experience as an educator of a techn ical cou r se in an integrated manner at the Federal Institute of Education, Science and Technology of Amazonas ( IFAM), Manaus Campus Center (CMC), to come across me with th e in clusion of deaf students in school and share doubts and concerns expressed by fel low peda g ogues and also teachers . So, the goal of the research was to understand how was the process of inclusion of deaf students in mid level technical courses in an int egra ted manner the IFAM/CMC. To do this, choose perform a qualitative study through a case st u dy. The data collection instruments used were interviews, field journal and wheel of conversation. For the analysis of the data we use content an alysis allowed us to identify three analytical categories finals: 1. Inclusive process and school real ity; 2. T he relevance of integrated pedagogical practices in school inclusion; 3. Policies and practical actions for the school inclusion of the deaf stud ent. For each cat egor y we developed an argumentative text to describe the developments brought by each categor y . In category inclusive process and school reality was evidenced characteristics such as isolation, lack of interaction, no field of sign languag e by listeners an d th e Portuguese language by deaf determining an inclusive process on school reality complex a nd partial yet. In the second category have identified as essential to the process inclusive teaching practices built via integrated planning for real feasibility of including the deaf student, having highlighted the methodological adaptations . Th e third c ategory treated on policies and practical actions for the inclusion of the deaf student school where it became apparent the demand by creating a policy of profess iona l training, educational, communicational, accessibility and pedagogical attitudin al need t o be solidified in school, in addition to being the center of attention to People with special educational Needs (NAPNE) as the primary inclusion policy of IFAM. In t his way, research has shown that there are several factors that need to be consid ered by t he school community the IFAM/CMC to develop an inclusive process for the student deaf ranging from the training of professionals who work with th ese students and scho ol community who plays with such students to the systematization of integrated pl anning t h at allows not only t he entry of that student in the institution, but your permanence and success. The unfolding of the three categories obtained led to the elabor atio n of a Didactic Guide school: adding Instructional deaf students and now what to do? that comes with the propo sal to contribute to the process of inclusion of deaf students in the regular school system through basic information, but ne vertheless releva nt a bout the context of school inclusion, history, language and deaf culture, pedagog ical pra c tices and suggestion s of proposals on the process of school inclusion of the deaf student.